2013
DOI: 10.1345/aph.1s002
|View full text |Cite
|
Sign up to set email alerts
|

Aclidinium Bromide: An Alternative Long-Acting Inhaled Anticholinergic in the Management of Chronic Obstructive Pulmonary Disease

Abstract: Aclidinium bromide is a novel, inhaled, long-acting anticholinergic that, when administered at the FDA-approved dose, safely produces clinically and statistically significant bronchodilation and improves health status in patients with moderate to severe COPD. Long-term clinical trials assessing the efficacy and safety of aclidinium are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
(67 reference statements)
0
9
0
Order By: Relevance
“…With regard to the tolerability profile, it should be noted that receptor selectivity and rapid plasma hydrolysis of aclidinium to inactive metabolites can explain the low incidence of systemic adverse events observed in clinical trials; such events, including anticholinergic side effects, were also generally mild [35, 36] (Table 1). …”
Section: Main Textmentioning
confidence: 99%
“…With regard to the tolerability profile, it should be noted that receptor selectivity and rapid plasma hydrolysis of aclidinium to inactive metabolites can explain the low incidence of systemic adverse events observed in clinical trials; such events, including anticholinergic side effects, were also generally mild [35, 36] (Table 1). …”
Section: Main Textmentioning
confidence: 99%
“…34 Clinical trials have demonstrated that aclidinium bromide provides a sustained bronchodilation similar to that observed with tiotropium bromide and confirmed the positive safety profile of aclidinium bromide, particularly in terms of a very low propensity to cause antimuscarinic adverse events. 5 Aclidinium bromide, administered in a multidose DPI (Genuair), is rapidly hydrolyzed once absorbed into the plasma, 31 which enhances its safety profile. 111 However, as its duration of action at the doses employed in phase III clinical trials does not provide a clinically significant bronchodilation over 24 h, inhaled aclidinium bromide has been proposed for registration and approved with a twice daily regimen.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
“…5 The predetermined dose of aclidinium bromide is 400 μg (equivalent to 343 μg of aclidinium), whereas each delivered dose, which is the amount of drug that leaves the inhaler, contains 375 μg of aclidinium bromide, equivalent to 322 μg of aclidinium. 5 The long-term efficacy and safety of aclidinium bromide were recently investigated in patients with moderate to severe COPD in two double-blind, placebo-controlled 52-week studies. 112 At 12 and 28 weeks, aclidinium bromide significantly improved trough FEV 1 compared with placebo, an effect which was maintained over the 52-week study period.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
See 2 more Smart Citations